Conducting public involvement in dementia research: The contribution of the European Working Group of People with Dementia to the ROADMAP project. (6th April 2021) - Diaz, Ana; Gove, Dianne; Nelson, Mia; Smith, Michael; Tochel, Claire; Bintener, Christophe; Ly, Amanda; Bexelius, Christin; Gustavsson, Anders; Georges, Jean; Gallacher, John; Sudlow, Cathie
Abstract: Background: Dementia outcomes include memory loss, language impairment, reduced quality of life and personality changes. Research suggests that outcomes selected for dementia clinical trials might not be the most important to people affected. Objective: One of the goals of the 'Real world Outcomes across the Alzheimer's Disease spectrum for better care: Multi‐modal data Access Platform' (ROADMAP) project was to identify important outcomes from the perspective of people with dementia and their caregivers. We review how ROADMAP's Public Involvement shaped the programme, impacted the research process and gave voice to people affected by dementia. Design: The European Working Group of People with Dementia (EWGPWD) were invited to participate. In‐person consultations were held with people with dementia and caregivers, with advance information provided on ROADMAP activities. Constructive criticism of survey content, layout and accessibility was sought, as were views and perspectives on terminology and key concepts around disease progression. Results: The working group provided significant improvements to survey accessibility and acceptability. They promoted better understanding of concepts around disease progression and how researchers might approach measuring and interpreting findings. They effectively expressed difficult concepts through real‐world examples. Conclusions: The role of the EWGPWD in ROADMAP was crucial, and its impact was highly influential. Involvement from the design stage helped shape the ethos of the programme and ultimately its meaningfulness. Public contribution: People with dementia and their carers were involved through structured consultations and invited to provide feedback on project materials, methods and insight into terminology and relevant concepts.